PIDANA PENJARA DALAM SISTEM PERADILAN PIDANA ANAK - I Dewa Ayu Yus Andayani (Fakultas Hukum Universitas Ngurah Rai, 2018)
Prison sentences are still the main choice for judges to impose criminal penalties for children in conflict with the law. This is because criminal prison sanctions are still regulated as sanctions in the juvenile justice system. The term imprisonment refers to the place where it is carried out and the type of criminal sanction. In normative provisions, Article 10 of the Criminal Code regulates the types of criminal sanctions, one of which is imprisonment. Prison sanctions are also used in the juvenile justice system as stipulated in Article 71 of Law Num- ber 11 of 2012 concerning the Criminal Justice System. Criminal restrictions on freedom are enforced in the event that a child commits a serious criminal of- fense or a criminal act accompanied by violence that must not exceed ½ of the maximum imprisonment that is threatened against adults.